Implementasi Design Thinking Dalam Perancangan Ui/Ux Aplikasi Kesehatan Berbasis Mobile (Studi Kasus: Pt. Sintasi) - Muhammad Fadhil Ar Rizqi; Kamal Prihandani; Apriade Voutama (Jurnal Ilmiah Wahana Pendidikan, 2023)
Health is a more concern, especially in the period after the COVID-19 pandemic then digitalization because the COVID-19 pandemic caused some services or poly in health facilities to temporarily switch from conventional to online. Medisin, which is a new product at PT Sintesa Inti Prestasi is here to develop its business to be more widespread and can make a real contribution to society and become a bridge between the general public and health business people in Indonesia through the Medisin application. To present an application that suits the needs of industry and society, the involvement of User Interface and User Experience (UI / UX) in designing Medisin applications. This study aims to produce application interface design using the design thinking method and find out the purpose of compounding and the evaluation results of this study and the results of research on medical application design in the testing section using a single ease question as the method shows the level of ease of user interface design results getting a final score of 6.5 with the score showing the prototype is in satisfactory results.